A Narrative Inquiry of College Students’ Gestures in Performing Public Speaking in ESP Class - Mulyadi, Cecylia Santi; Setyaningrum, Rina Wahyu (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This research aims to explore how college students use gestures while performing public speaking activities in an English for Specific Purposes (ESP) class. The study focuses on students’ lived experiences and the meanings they attach to their body movements during English speech performances. To address this aim, the research employs a narrative inquiry approach, which is suitable for examining personal experiences and subjective interpretations of nonverbal behavior in speaking contexts. Data were collected through classroom observations and in-depth interviews with selected ESP students who had delivered presentations or speeches in English. Classroom observations were conducted to identify patterns of gestures used during speaking, while interviews allowed students to reflect on their feelings, intentions, and awareness of their body movements. The collected narratives were analyzed thematically to explore the relationship between gestures, emotional expression, communication strategies, and speaking confidence. The findings indicate that gestures play an important role in students’ public speaking performances. Gestures were used to emphasize ideas, clarify messages, and support verbal explanations. At the same time, gestures also reflected students’ psychological states. Anxious gestures, such as fidgeting, repetitive hand movements, or self-touching, were commonly associated with nervousness and lack of confidence. In contrast, open and controlled gestures were linked to higher levels of confidence, engagement, and audience connection. Overall, this study highlights the importance of nonverbal communication awareness in ESP classrooms and suggests that integrating instruction on gestures and body language into public speaking practice may enhance students’ confidence and communicative effectiveness.